2022
DOI: 10.1371/journal.pntd.0010146
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a structured treatment discontinuation in patients with inoperable alveolar echinococcosis on long-term benzimidazole therapy: A retrospective cohort study

Abstract: Objectives Alveolar echinococcosis (AE) is an orphan zoonosis of increasing concern in endemic areas, including Europe. It frequently presents in an advanced, inoperable stage, that requires life-long parasitostatic benzimidazole therapy. In some patients, long-term therapy leads to negative anti-Em18 antibody ELISA and PET. It is disputed, whether these patients are truly cured and treatment can be safely discontinued. Our aim was to retrospectively assess long-term outcome of 34 patients with inoperable AE w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…Currently, the Em18 antigen has been mainly used for the follow-up of AE patients under long-term benzimidazole therapy. Negativity of anti-Em18 antibodies for at least two years is one of the parameters used to determine, if benzimidazole therapy in inoperable AE patients can be stopped ( Ammann et al., 2015 ; Deibel et al., 2022 ). Thereby, the Em18 antigen seems to be vital for biological functions and the viability of especially E. multilocularis metacestodes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the Em18 antigen has been mainly used for the follow-up of AE patients under long-term benzimidazole therapy. Negativity of anti-Em18 antibodies for at least two years is one of the parameters used to determine, if benzimidazole therapy in inoperable AE patients can be stopped ( Ammann et al., 2015 ; Deibel et al., 2022 ). Thereby, the Em18 antigen seems to be vital for biological functions and the viability of especially E. multilocularis metacestodes.…”
Section: Discussionmentioning
confidence: 99%
“…These two antigens are immunologically most likely identical and can be used for a serological parasite-viability assessment after long-term therapy with albendazole in AE patients. A negative II/3-10 or Em18 antibody serology is correlated to a positive treatment outcome and clinical remission in combination with PET-CT ( Ammann et al., 2015 ; Deibel et al., 2022 ; Gottstein et al., 2019 ; Hotz et al., 2022 ). In immunohistochemistry with polyclonal rabbit antibodies directed against the II/3 antigen, the germinal layer and protoscoleces can be visualized.…”
Section: Introductionmentioning
confidence: 99%
“…Given the unavailability of serum samples, it is still unclear whether TER ATPase is suitable for early diagnosis of human echinococcosis. The Em18 antigen is known to be a valid marker for follow-up [ 50 ]. Our results showed that, for cured patients, both TPx-1 and TER ATPase had a higher positive rate than the recombinant Em18 protein.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of initial presentation, eosinophilia in the blood is more likely to be seen in CE and is rarely found in AE. All in all, the established markers' total IgE and eosinophil granulocyte counts are limited due to their low sensitivity in CE, but even more limited in AE [10]. The eosinophil cationic protein (ECP) could represent a new promising routine marker measured in serum.…”
Section: Echinococcosis Is a Zoonosis Caused By Infection With A Tape...mentioning
confidence: 99%